2020
DOI: 10.2174/2210327909666190129154802
|View full text |Cite
|
Sign up to set email alerts
|

Routing Algorithm based on Clustering for Increasing the Lifetime of Sensor Networks by Using Meta-Heuristic Bee Algorithms

Abstract: Background: Nowadays, the use of wireless sensor networks is developing rapidly. these networks are applicable in many fields, including military, medical, and environment. these networks use hundreds or thousands of cheap sensor nodes with low power-low and low energy to perform large tasks. These networks have limitations that can lead to inefficiency or not cost - effective. Among these limitations, consumption of energy and issues related to the lifetime of the network. One of the solutions that can assist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…ey believe that it can assist in load balancing between effector nodes, increase scalability, and improve energy consumption [4], thereby extending the life of the Internet, clustering effector nodes, and placing appropriate cluster heads in all clusters. Choosing the correct cluster head can greatly reduce the energy consumption of the Internet and prolong the life of the Internet [5]. In their research, Bhola et al have shown that the unconnected effector Internet (WSN) often contains a large number of effector nodes, which can collect numbers in different situations.…”
Section: Introductionmentioning
confidence: 99%
“…ey believe that it can assist in load balancing between effector nodes, increase scalability, and improve energy consumption [4], thereby extending the life of the Internet, clustering effector nodes, and placing appropriate cluster heads in all clusters. Choosing the correct cluster head can greatly reduce the energy consumption of the Internet and prolong the life of the Internet [5]. In their research, Bhola et al have shown that the unconnected effector Internet (WSN) often contains a large number of effector nodes, which can collect numbers in different situations.…”
Section: Introductionmentioning
confidence: 99%
“…A wireless sensor network is made of many sensor nodes distributed in the desired environment. In many wireless sensor networks applications, sensor nodes are distributed in a random manner and unplanned in the environment [2]. The sensors are in charge of sensing, collecting, and processing their surroundings' data and sending them to the center or the sink.…”
Section: -Introductionmentioning
confidence: 99%